Sublingual versus vaginal use of Misoprostol for induction of labor - Bansal, Mamta; Sharma, Indu; Lagoo, Jyoti; Jadhav, Harish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Induction of labor is one of the great challenges for obstetric care provider. Misoprostol is used for induction of labor by various routes with the advantages in being cheap and stable at room temperature and widely available even in resource-poor settings. Methods: A randomized controlled study was conducted in the obstetrics and gynecology department of Govt. Medical College and associated Maharani Hospital, Bastar, Chhattisgarh, India over a period of 1.75 years from September 2014 to May 2016. Study has comprised of 200 pregnant women admitted in the department for induction of labor fulfilling the inclusion and exclusion criteria. Data was collected and analyzed by SPSS 16.0. z-test and chi-square test to compare the safety and efficacy of both the routes of misoprostol use for IOL. Results: There were insignificant differences in number of doses required for induction with satisfactory maternal and neonatal outcome but shorter (12 hours) induction delivery interval with sublingual Misoprostol induction. Most of the cases of both the groups were delivered by vaginal route (86% and 62%) within 12 hours of induction(58% and 42%) yet significant (p value < 0.001) number of cases had undergone caesarean in group of vaginal misoprostol administration (29%) with major indications of meconium stained liquor (3% and 12%) and non assuring fetal heart rate (1% and 10%). Conclusions: Although both the routes of induction by Misoprostol are well tolerated by the women with satisfactory neonatal outcome, sublingual Misoprostol has an added advantage of quicker delivery, less caesarean and ease of administration indicates better safety and effectiveness.